Pharmacotherapy of the most frequent headaches in adults - Zidverc-Trajković Jasna (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2019)
Tension-type headache, migraine, cluster headache and medication overuse headache are the most frequent headaches in adults. First-line treatments for migraine attack are nonsteroidal anti-inflammatory drugs and triptans, and metoprolol, propranolol, topiramate, valproates and flunarizine (not registered in Serbia) for prophylactic therapy. Nonsteroidal anti-inflammatory drugs are recommended for attacks of tension-type headache and amitriptyline, mirtazapine and venlafaxine as prophylactic therapy. Cluster headache attack should be treated with oxygen, sumatriptan or zolmitriptan, while verapamil and prednisone are efficacious as prophylactics for episodic and lithium carbonate for chronic form of the disorder. Medication overuse headache is treated by withdrawal of overused medication with or without introduction of prophylactic treatment. Careful selection of drugs is needed for pregnancy and lactation, as well as for elderly patients.